2011
DOI: 10.1007/s00595-011-0072-x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic resection for gastrointestinal stromal tumors in the stomach

Abstract: Endoscopic ultrasound-guided FNAB is recommended for definite preoperative diagnosis of histopathologically unknown SMTs to determine the indications for surgery. The laparoscopic approach with the assistance of endoscopy is useful for improving the curability, with minimal invasiveness for the partial resection of GISTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…To prevent stenosis after resection by the removal of excessive normal tissue, the direction of the stapler should be perpendicular to the long axis of the stomach, and multiple staplers may be needed. When stenosis is anticipated even with this method, for example, with a 5 cm tumor in the anterior wall of the antrum, the so-called "eversion technique" can be applied 84,85. A gastrotomy is made either proximally or distally with a gross negative margin of normal mucosa about half the length of the circumference of the tumor.…”
Section: Laparoscopic Surgical Technique Based On Tumor Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent stenosis after resection by the removal of excessive normal tissue, the direction of the stapler should be perpendicular to the long axis of the stomach, and multiple staplers may be needed. When stenosis is anticipated even with this method, for example, with a 5 cm tumor in the anterior wall of the antrum, the so-called "eversion technique" can be applied 84,85. A gastrotomy is made either proximally or distally with a gross negative margin of normal mucosa about half the length of the circumference of the tumor.…”
Section: Laparoscopic Surgical Technique Based On Tumor Locationmentioning
confidence: 99%
“…After cutting the gastric wall using either energy-based devices or electrocautery, the defect in the gastric wall is approximated together with the stay sutures and hanged up, or a defect and normal mucosa attached to the tumor are lifted up together in an eversion technique. Finally, a linear stapler completes the resection while the endoscopy is kept in the GE junction to prevent stenosis 84,91,92…”
Section: Laparoscopic Surgical Technique Based On Tumor Locationmentioning
confidence: 99%
“…The goal of the surgery was tumour removal with tumour-free margins wider than 1 cm, controlled histologically (table 3). Tumours measuring more than 6 cm and being located in the posterior wall of the stomach as well as other technical difficulties limited the possibility of laparoscopic intervention [4]. However, our clinical experience showed that in some cases these tumours can be removed endoscopically, which is why surgeons support the initiative of gastroenterologists to perform such procedures for selected patients.…”
Section: Resultsmentioning
confidence: 99%
“…Tumour-free margins of 1–2 cm were recommended several years ago [16]. Tumours measuring 2–5 cm are recommended to be removed laparoscopically [4,17]. Regional lymphadenectomy is generally not required since GISTs rarely (<5%) metastasize to the lymph nodes [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…and Sakamoto et al . reported LWR techniques for gastric submucosal tumor (SMT) . These techniques are the basis of LWR for gastric GIST, but they were originally employed for whole‐layer dissection of the stomach wall.…”
Section: Discussionmentioning
confidence: 99%